(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Since Internet became in the last years the biggestsource of information as open sources and free market and commonly reachablefor the educationalist in higher and further education systems, the bookconcept has been dramatically redefined for higher education and furthereducation, especially in terms of separating of its content and the related support.Practically, when using the electronic media, a book could take a differentlook-the electronic book (e-book). Due to their widely spreadin the last period, the e-books are one of the most effective ways to supportdistance learning (e-learning), as they can be read by thousands of readers.Due to the fact that the teachers have limited time for participating to theface-to-face training programmes, the e-books became an important tool forpromoting different training courses organized in the frame of variousprojects. The various types of engagement in digital libraries (DLs), such asfunding developmental stages or devoting important shares in the acquisition ofaccess has drawn considerable attention to the evaluation of these systemsduring the late period. The term digital library is vast, covers many anddifferent applications and has been used interchangeably for systems, likedigitized collections, e-journals platforms, network databases, librarywebsites, etc. Moreover the current electronic publishing business modelsenrich the DL technology aiming to provide powerful information access optionsto the users. The best practices and experiences of the teachers who achievedthe on-line courses were collected and help the partnership to design aweb-guideline entitled “Best Practices Guideline for Educational Use of ICTTools” as a final output of the project. The content of the European course andthe web-guideline have been produced as an e-book format by using Desktop Author software application.In this sense, the paper aims to present the most important features proposedby Desktop Author softwareduring the design process of the mentioned e-books, together with the mainfacts presented by the related e-volumes. The advent of electronic books(e-books) has significantly impacted the publishing industry in recent years.The prevalence of e-books has prompted many publishers to reconsider theirdistribution channels for new titles. They need to decide whether to sell thee-book version of new titles. We derive the conditions under which a publishershould sell only printed books (p-books), only e-books, and both of themsimultaneously.